2007
DOI: 10.1002/anie.200603810
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Enantioselective Aziridination of α,β‐Unsaturated Aldehydes

Abstract: Simple chiral amines catalyze a highly chemo‐ and enantioselective aziridination of α,β‐unsaturated aldehydes to provide 2‐formylaziridines in good yields and with up to 99 % ee. The synthetic utility of this organocatalytic method was exemplified in a two‐step asymmetric synthesis of β‐amino acid esters with readily removable protecting groups (see scheme; R1=tert‐butoxycarbonyl, benzyloxycarbonyl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 228 publications
(65 citation statements)
references
References 76 publications
2
62
0
1
Order By: Relevance
“…[25] This has led to the development of aminocatalytic aziridinations of a,bunsaturated aldehydes and ketones. [26][27] Herein, we report the development, the substrate scope, and one-pot applications of the amine-catalyzed enantioselective aziridination of a,b-unsaturated aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…[25] This has led to the development of aminocatalytic aziridinations of a,bunsaturated aldehydes and ketones. [26][27] Herein, we report the development, the substrate scope, and one-pot applications of the amine-catalyzed enantioselective aziridination of a,b-unsaturated aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…The same type of reaction mechanism has also been observed in the organocatalytic asymmetric epoxidation of enals [12l,o] and asymmetric aziridination of enals. [17] In summary, we report a new example of a highly chemo-and enantioselective organocatalytic cyclopropanation of a,b-unsaturated aldehydes. The reaction was efficiently catalyzed by simple chiral pyrrolidine derivatives and gives the corresponding 2-formylcyclopropanes in high yields with 9:1 to > 25:1 dr and 93-99 % ee.…”
mentioning
confidence: 98%
“…[14] We have applied diphenylprolinol silyl ether to the reaction of a,b-unsaturated aldehydes with enecarbamates and found that a formal aza [3+3] cycloaddition reaction proceeds in a highly enantioselective manner as reported herein (Figure 1). …”
mentioning
confidence: 62%